2004
DOI: 10.1007/s10329-004-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Grooming relationships of adolescent orphans in a free-ranging group of Japanese macaques (Macaca fuscata) at Katsuyama: a comparison among orphans with sisters, orphans without sisters, and females with a surviving mother

Abstract: The present study examined grooming relationships of adolescent females in a free-ranging group of Japanese macaques (Macaca fuscata) at Katsuyama. To assess whether the loss of the mother influenced the grooming relationships of adolescent females (5-7 years old), we compared the time spent in grooming interactions and the number of grooming partners among the following three groups: 6 adolescent orphans with sisters, 9 adolescent orphans without sisters, and 11 adolescent non-orphans with surviving mothers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…On the other hand, Lemur catta with dental impairment, engaged in more feeding time during a period of the day when others tended to rest [Millette et al, 2009]. Hands are normally used to perform many life-sustaining activities; in addition to feeding and climbing, hands are usually used for both auto and allogrooming, behaviors that are important socially and in terms of reduction of ectoparasite burdens [Nakamichi and Shizawa, 2003;Tanaka, 1995;Tanaka and Takefushi, 1993;Yamada et al, 2005]. Furthermore, physical impairment has potential consequences for locomotor ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Lemur catta with dental impairment, engaged in more feeding time during a period of the day when others tended to rest [Millette et al, 2009]. Hands are normally used to perform many life-sustaining activities; in addition to feeding and climbing, hands are usually used for both auto and allogrooming, behaviors that are important socially and in terms of reduction of ectoparasite burdens [Nakamichi and Shizawa, 2003;Tanaka, 1995;Tanaka and Takefushi, 1993;Yamada et al, 2005]. Furthermore, physical impairment has potential consequences for locomotor ability.…”
Section: Introductionmentioning
confidence: 99%
“…CLMs can affect manual functionality, dexterity, and the ability to grasp objects. Hands are normally used to perform many life-sustaining activities; in addition to feeding and climbing, hands are usually used for both auto and allogrooming, behaviors that are important socially and in terms of reduction of ectoparasite burdens [Nakamichi and Shizawa, 2003;Tanaka, 1995;Tanaka and Takefushi, 1993;Yamada et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the degree of kinship across the newly formed groups, we assessed the closest living relative of each individual (Table 2 ). Which individual was regarded as the closest living relative was based on the care providing function during the ontogeny of infants and juveniles in Japanese macaques (MacDonald Pavelka et al, 2002 ; Nakamichi, Onishi et al, 2010 ; Nakamichi & Yamada, 2010 ; Nozaki, 2009 ; Yamada et al, 2005; 2005 ). If the mother of a male was still alive, she would be the closest care‐providing relative and therefore included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…At Takasakiyama, according to Itani (1959), high-ranking adult males cared for infants during the birth season. On the other hand, at Katsuyama, Yamada et al (2005) found that adolescent orphans without sisters spent more time grooming with same-aged females as well as other unrelated adult females.…”
Section: Introductionmentioning
confidence: 93%